SYNTHESIS AND PROPERTIES OF ETHOXYLATED GLYCEROL MONOOLEATE AS PALM OIL BASED NONIONIC SURFACTANTS - Indri Badria Adilina; Egi Agustian; Yenny Meliana; Anny Sulaswatty (Research Center for Chemistry - LIPI, 2015)
Palm oil based nonionic surfactants were synthesized by reacting glycerol monooleate with ethylene oxide at 80 ÂºC in the prescence of an alkaline catalyst. Purification of the products was conducted by use of acetic acid and black carbon which gave ethoxylated products (EGMO) with a higher level of viscocity and greater solubility in water. Physical and chemical properties of the product such as surface activity, cloud point, acid value, ester value, hydroxyl value, and hydrophilic-lipophilic balance was also determined and results varied depending on the reagent molar ratio. The synthesized EGMO were soluble in water and therefore show potential use as surface active agents in personal care and cosmetic products.Keywords:Â Â nonionic surfactant, ethoxylation, glycerol monooleate, palm oil